2019
DOI: 10.1109/tcyb.2018.2834466
|View full text |Cite
|
Sign up to set email alerts
|

A Clustering-Based Adaptive Evolutionary Algorithm for Multiobjective Optimization With Irregular Pareto Fronts

Abstract: Existing multiobjective evolutionary algorithms (MOEAs) perform well on multiobjective optimization problems (MOPs) with regular Pareto fronts in which the Pareto optimal solutions distribute continuously over the objective space. When the Pareto front is discontinuous or degenerated, most existing algorithms cannot achieve good results. To remedy this issue, a clustering-based adaptive MOEA (CA-MOEA) is proposed in this paper for solving MOPs with irregular Pareto fronts. The main idea is to adaptively genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(42 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…where P represents the true PF solutions, P * stands for the optimal solutions generated from the algorithm, and |P| is the number of the true PF. Specifically, Table 6 contains a comparison among MOWOATS, CA-MOEA, MOEA/D, EMyO/C, RVEA*, NSGA-II, and NSGA-III according to IGD metric computed according to Equation (27) [34]. The results confirm that MOWOATS reaches the lowest mean values of the IGD metric for all test functions, except for DTLZ73, for which it yields the second rank.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…where P represents the true PF solutions, P * stands for the optimal solutions generated from the algorithm, and |P| is the number of the true PF. Specifically, Table 6 contains a comparison among MOWOATS, CA-MOEA, MOEA/D, EMyO/C, RVEA*, NSGA-II, and NSGA-III according to IGD metric computed according to Equation (27) [34]. The results confirm that MOWOATS reaches the lowest mean values of the IGD metric for all test functions, except for DTLZ73, for which it yields the second rank.…”
Section: Resultsmentioning
confidence: 70%
“…Another feature which strains the quality of solutions computed by a MOP solver occurs when the PF exhibits an irregular shape. There have been some works in the literature that address this issue in particular, such as the Clustering-based Adaptive Multi-Objective EA (CA-MOEA) by Hua et al [34], who suggested using a clustering-based method to overcome those problems with irregular PF shapes. The use of clustering helps to diversify the tentative solutions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pareto optimal solutions of these problems are distributed only in part of the objective space. Several characteristics make such problems more difficult to solve than problems with regular Pareto fronts [5,6]. Firstly, since the distribution of Pareto front is unknown, it is hard to identify the real Pareto front area.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, algorithms based on clustering or space division. In our recent work [6], a clustering based multi-objective evolutionary algorithm called CA-MOEA was proposed, which adaptively generates a set of cluster centers in the current population as the reference points to maintain diversity and accelerate convergence for problems with irregular Pareto fronts. However, as CA-MOEA is mainly based on non-dominated sorting, it encounters resistance in dealing with many-objective problems.…”
Section: Introductionmentioning
confidence: 99%